Pelestarian Budaya melalui Media Sosial TikTok untuk Membentuk Karakter Cinta Tanah Air Siswa SMK Karanganyar - Mila Rosita Anggraini; Obby Taufik Hidayat (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2026)
This study aims to describe the use of TikTok social media in cultural preservation and its implications for fostering students’ patriotism character in vocational high schools in Karanganyar. This research employed a qualitative approach with a case study design to explore students’ perceptions and experiences in depth. Data were collected through in-depth interviews, observations, and documentation involving teachers and students actively using TikTok in cultural learning activities. The findings indicate that TikTok utilization enhances students’ awareness of cultural preservation through creative, innovative, and contextual digital content. Initially, students perceived TikTok as a platform for entertainment and academic purposes; however, through the learning process, this perception gradually shifted toward viewing it as an effective educational medium that supports the dissemination of cultural values. The development of patriotism character occurs through stages of introduction, understanding, and implementation in daily life. Furthermore, students’ active involvement in creating cultural content increases creativity, strengthens their sense of pride in local culture, and encourages cultural preservation. Therefore, TikTok can serve as a relevant and effective learning medium to support cultural preservation and strengthen national character in the digital era.